XVIIth International Congress on Mathematical Physics 2013
DOI: 10.1142/9789814449243_0017
|View full text |Cite
|
Sign up to set email alerts
|

Entropy, Chaos and Weak Horseshoe for Infinite Dimensional Random Dynamical Systems

Abstract: Abstract. In this paper, we study the complicated dynamics of infinite dimensional random dynamical systems which include deterministic dynamical systems as their special cases in a Polish space. Without assuming any hyperbolicity, we proved if a continuous random map has a positive topological entropy, then it contains a topological horseshoe. We also show that the positive topological entropy implies the chaos in the sense of Li-Yorke. The complicated behavior exhibiting here is induced by the positive entro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Thus, with a positive entropy, Lian and Young's result implies that the hyperbolic system has a horseshoe. The existence of SRB measures also yields that the partially hyperbolic attractor is chaotic and contains a full weak horseshoe following from the recent result by Huang and Lu [16] since the entropy is positive. By a full horseshoe of two symbols we mean that there exist subsets U 1 , U 2 of Hilbert space H such that the following properties hold (1) U 1 and U 2 are non-empty bounded closed subsets of H and d(U 1 , U 2 ) > 0.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, with a positive entropy, Lian and Young's result implies that the hyperbolic system has a horseshoe. The existence of SRB measures also yields that the partially hyperbolic attractor is chaotic and contains a full weak horseshoe following from the recent result by Huang and Lu [16] since the entropy is positive. By a full horseshoe of two symbols we mean that there exist subsets U 1 , U 2 of Hilbert space H such that the following properties hold (1) U 1 and U 2 are non-empty bounded closed subsets of H and d(U 1 , U 2 ) > 0.…”
Section: Introductionmentioning
confidence: 73%
“…Remark: With a positive entropy, Lian and Young's result implies that the hyperbolic system has a horseshoe. The existence of SRB measures also yields that the partially hyperbolic attractor is chaotic and contains a full weak horseshoe following from the recent result by Huang and Lu [16] since the entropy is positive.…”
Section: Introductionmentioning
confidence: 73%
“…The notion of weak horseshoe first appeared in [7] (see also [8,9]). We introduce several kinds of weak horseshoes in the following.…”
Section: Introductionmentioning
confidence: 99%
“…For a flow (M, φ), it is well known that h top (φ t ) = |t|h top (φ 1 ) for any t ∈ R (see [1]). In [8], Huang and Ye showed that a TDS (X, T ) has positive topological entropy if and only if (X, T ) has a weak horseshoe with positive density hitting times (see also [7,9]). Thus, it is clear that for a flow (M, φ), if the time one map (M, φ 1 ) has a weak horseshoe with positive density hitting times then (M, φ τ ) has the same property for all τ = 0.…”
Section: Introductionmentioning
confidence: 99%